ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI ASEAN MEMBER COUNTRIES PADA TAHUN 2011-2016 - Sari, Agatha Christy Permata; Kaluge, David (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
Economic Growth becomes the important factor to measure how success economic state. Therefore, many country will always try to increase their economic growth for the priority target that must be reached.this research has purpose to present which factor that can influence economic growth in ASEAN member countreias.t There is 10 countries being the sampe country, which is Indonesia, Thailand, Malaysia, Singapore, Philippines,Brunei Darussalam, Vietnam, Laos, Myanmar,and Cambodia. This research use Panel Data Regression, Generalized Least Square (GLS) method and fixed-effect estimation model by using analytical tools help in processing the data which uses Eviews 9 programm. Data is panel data of all ASEAN member countries in 6 year period (2011-2016). Varible that used are : GDP, Import, Export, Foreign Direct Inverstment, Competitiveness Index, Government Expenditure, and Labor force. The result is each independent variable can explain 99,4126% of dependen variable. Which is, IM (import) variable is the only one variable that has positive significant influence to economic growth. The finding from this research is economic growth phenomenon that occurred in ASEAN is greatly influenced by consumption rather than investment and production. So, almost the entirety of economic growth can be measured by consumption side.